KNOWLEDGE, ATTITUDE AND PRACTICE ABOUT CARE OF FEED CHILDREN OF MOTHERS WITH CHILDREN BELOW 5 YEARS OLD INPATIENT TREATMENT AT VINH THUAN DISTRICT HEALTH CENTER IN 2021 (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe the current state of knowledge, attitude and practice on caring forfebrile children of mothers whose children under 5 years of age are inpatient at Vinh Thuandistrict health Center in 2021.Research methoddology: A cross-sectional descriptive study using quantitative researchmethods, distributing questionnaires and interviewing mothers with children under 5years of age inpatient treatment at Vinh Thuan District Health Center in 2021 with a set ofquestionnaires suitable presets.Results: Research on knowledge, the percentage of mothers who give the wrong concept offever accounts for nearly 3 times as many mothers with the right concept. Hot baby sign isthe most obvious sign of mothers, accounting for a high rate from 86%. Most mothers knowthat convulsions are a complication of fever, accounting for a high rate 86%.In terms of practice attitude, all mothers know that fever is a dangerous problem and need tobe taken care of in children, accounting for 100%. When detecting fever in children, mothersknow to feed their children many meals (46.7%) and drink more juice (20%).Conclusion: Regarding knowledge, 73.3% of mothers understood the concept of feverincorrectly. More than 90% of mothers recognize a child’s fever based on the signs of thebaby being cranky and fussy. About the attitude of practice, about 46.7% of mothers gavetheir children many meals when they had a fever and 20% gave them fruit juice to drink.
Keywords: Knowledge, attitude and practice on caring for febrile children of mothers with children under 5 years of age being treated.